Texas history - Teja, Jesús F. de la; Garnier, Vaerie; Green, Kerry; Harman, Kristin; Shaw-Kelly, Aderienne (Houghton Mifflin Harcourt, 2016)
The geographer's tools -- A land called Texas -- The regions of Texas -- Texas Indians, beginnings-1700 -- The age of contact, 1492-1670 -- The Spanish colonial period, 1680-1760 -- Conflicts of empire, 1760-1821 -- Texas on the Mexican frontier, 1820-1835 -- Life in Mexican Texas, 1820-1835 -- The road to revolution, 1825-1835 -- The Texas revolution, 1835-1836 -- A new nation, 1836-1845 -- Life in the republic, 1836-1845 -- Texas faces foreign challenges, 1836-1845 -- Texas joins the United States, 1845-1860 -- Western expansion and conflict, 1845-1860 -- Life in a frontier state, 1845-1861 -- Texas and the Civil War, 1861-1865 -- Reconstruction, 1865-1877 -- The Indian wars, 1861-1880 -- The cattle kingdom, 1860-1890 -- Railroads and farming, 1870-1900 -- The oil boom, 1890-1920 -- Texas in the age of reform, 1870-1920 -- Texans at home and abroad, 1890-1920 -- Boom and bust, 1920-1939 -- World War II and the Cold War, 1939-1960 -- Texas in transition, 1960-1980 -- Contemporary Texas, 1980-present -- Texas government, 1945-present -- Local government and citizenship, 1845-present -- The Texas economy -- The governors and presidents of Texas -- The Constitution of Texas -- Facts about Texas -- Atlas -- Glossary -- Spanish Glossary/Glosario